Beban Ekonomi Transplantasi Ginjal sebagai Terapi Pengganti Ginjal pada Pasien Penyakit Ginjal Kronik Stadium Akhir: Tinjauan Sistematis - Qurrata Akyuni; Dwi Endarti; Auliya Abdurrohim Suwantika; Wening Wulandari (Journal of Pharmaceutical and Sciences, 2026)
End-stage renal disease (ESRD) imposes a substantial economic burden on healthcare systems worldwide, extending well beyond its clinical implications. This burden is predominantly attributable to the requirements of renal replacement therapy (RRT), with kidney transplantation representing one of the most cost-intensive components of ESRD management. The complexity and continuity of long-term care needs further amplify the financial pressure on health systems globally. This systematic review was undertaken to identify and evaluate the economic burden associated with chronic kidney disease (CKD) across various RRT modalities, namely hemodialysis, peritoneal dialysis, and kidney transplantation, within diverse healthcare contexts. A systematic literature search was conducted in Scopus, PubMed, SpringerLink, and ProQuest, encompassing English-language observational studies and economic evaluations published between 2015 and 2025 that reported direct medical costs, non-medical costs, productivity losses, and related economic indicators. A total of 15 studies from multiple countries were analyzed, revealing a broadly consistent pattern of findings. Healthcare expenditures were found to escalate markedly with advancing CKD stage and the initiation of RRT. Multiple economic evaluation frameworks were employed, including disease burden analysis, cost-benefit analysis, comparative cost analysis, and cost-utility analysis. Hemodialysis incurred the highest annual costs, followed by peritoneal dialysis. While kidney transplantation requires a greater upfront investment, it has considerably lower long-term annual costs than continuous dialysis. The review ultimately affirms that kidney transplantation constitutes a more economically efficient therapeutic strategy for ESRD management, with meaningful potential to alleviate the broader global economic burden associated with this condition.